Pengaruh Program Loyalitas terhadap Kesetiaan Konsumen pada Industri Halal di Yogyakarta - Adha, Mufti Alam; Wahyudi, Rofiul; Nahar, Faiza Husnayeni (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2018)
This study aims to examine the effect of perceived benefits of loyalty programs, which include: financial benefits, social benefits, hedonic benefits, symbolic benefits of loyalty programs in the Halal Industry. This study also examined the effect of loyalty programs on brand loyalty. This research was conducted using a quantitative approach, namely by conducting surveys, online with a sample of 200 respondents. The data in this study were processed using the Structural Equation Modeling (SEM) analysis version 21. The results showed that the financial benefit variables, social benefits, symbolic benefits had a significant positive effect on loyalty programs. While the hedonic variable on loyalty programs shows a negative relationship. This study also confirms the significant positive effect of the loyalty program on brand loyalty.